The Influence of Local Culture on Intention to Recommend through Destination Image - Indra Iryanto Nur Hidayat; Wisnalmawati Wisnalmawati; Dyah Sugandini (Strata Business Review, 2023)
The main objective of this study is to explore how local culture affects recommendation intention among tourists who have visited Kebondalem Kidul Cultural Tourism Village, with destination image acting as a mediating factor. This research utilizes a quantitative and descriptive-analytical approach, using a 5-point Likert scale for measurement. Non-probability sampling, specifically convenience sampling, was used to collect primary data. The sample consisted of 200 tourist respondents who had visited the Kebondalem Kidul Cultural Tourism Village. Structural Equation Modeling (SEM) with SmartPLS 3.2.9 was used as the analysis tool. The findings of this study indicate that local culture directly influences tourists' recommendation intention and destination image when visiting Kebondalem Kidul Cultural Tourism Village. In addition, destination image is a partial mediating factor between local culture and recommendation intention for tourists in this cultural tourism destination. Destination image is the strongest predictor in influencing tourists' recommendation intention.